PERTANGGUNGJAWABAN PT MAHKOTA SENTOSA UTAMA AKIBAT WANPRESTASI DALAM JUAL BELI APARTEMEN MELALUI SISTEM PRE-PROJECT SELLING - Ayu Husna Nanda (Prodi Ilmu Hukum Fakultas Hukum Universitas Warmadewa, 2023)
High population growth causes the availability of residential land to be less and less, making people switch to vertical housing. This provides an opportunity for property developers to conduct business and attract consumers with a pre-project selling system or properties that are marketed in the form of new designs. However, there are still developers who have not fulfilled the requirements of Law Number 20 of 2011 concerning Flat Houses, so that potential customers are in a risky situation and cause defaults such as those made by PT Mahkota Sentosa Utama. This research aims to discuss the sale of property through pre-project selling conducted by PT Mahkota Sentosa Utama has been in accordance with the positive law in force in Indonesia or not and discuss the form of PT Mahkota Sentosa Utama's responsibility for default and losses to consumers related to apartment units that have been built or not yet built. The research method used is normative juridical research, which refers to legal principles and norms that are examined through a statutory approach by analyzing related regulations as the basis for the author's analysis, a conceptual approach as a basis for preparing legal arguments, a case approach by examining a specific problem through in-depth data review which aims to find the truth about the legal issues studied. The results of the research explain that the sale of property by PT Mahkota Sentosa Utama through the pre-project selling system has not complied with the provisions of positive law in Indonesia and includes non- compliance with administrative and licensing requirements, as well as the conditions for the sale and purchase binding agreement so that the result of not complying with legal provisions is that the sale and purchase binding agreement between PT Mahkota Sentosa Utama and consumers is considered null and void. Efforts to resolve default problems are payment of compensation costs and homologation agreements. In addition, it is important for developers to establish a transparent relationship with consumers.